“Practicing Translating Makes Me Autonomous!”: Indonesian EFL Learners’ Attitude on Translation Strategy in ELT - Adriani Yulia Purwaningrum (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
The implementation of translation strategy has become a significant issue in several countries amidst the constant discussion of technology integration in language learning. Although it has long been regarded as not reliable by some researchers since it is highly associated with grammar-translation methods, several EFL countries still regard translation strategy as an interactive learning strategy which focuses on learners. Therefore, the present study aims to investigate the attitude of EFL learners in a rural area in Indonesia towards the implementation of translation strategy in language learning. It also attempts to find out whether translation strategy is effective to foster learner autonomy. Applying a qualitative case study to a group of high school students from a rural area in Indonesia, questionnaires and focus group interviews were used to collect the data. The result showed that the participants perceived translation as a useful learning strategy to foster learner autonomy in an EFL context since it encouraged them to work collaboratively instead of depending on the teacher.